Uji Kinerja Turbin Francis Skala Laboratorium dengan Variasi Bukaan Katup - Mukhri, Zulfian; Zainuddin (CV. IRA PUBLISHING, 2022)
Francis turbine is a type of water turbine which is used to convert the potential energy of water into mechanical energy. Improved performance on the Francis turbine is influenced by several factors, one of which is by adjusting the opening of the water valve that will enter the turbine runner. The arrangement of the opening of the water valve that enters the turbine runner is very important to improve the performance of the Francis turbine. The setting of the valve opening of the Francis turbine is useful for obtaining optimization values ​​from the Francis turbine test. In this Francis turbine test, the valve opening is adjusted with an opening of 90°, 75°, 60°, 45°. From the results of this study, it was found that 90° valve opening produces 112.855 W turbine power, 75° valve opening produces 102.801 W turbine power, at 60° valve opening produces 95.287 W turbine power and at 45° valve opening produces turbine power of 82.608 W. The best performance is obtained from 90° valve opening because the turbine power generated is greater.